The expression of Cx43, TGFβ/smads signaling pathways and PCNA in the occurrence and development of gastric carcinoma and the relationship among them - Li, Chun-Hui; Pan, Li-Hui; Liu, Hai-Wang; Sahi, Rajina; Zhao, Xing; Cheng, Yu (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: To detect the protein expression level of Cx43, smad4 and PCNA in normal and gastric carcinoma tissue by immuno-histochemistry, western blotting and RT-PCR method. We intend to reveal the relationship between their expression in occurrence and development. Simultaneously through analyzing experimental data we have obtained the correlation among them. Materials and Methods: Immuno-histochemistry and western blotting were adopted to detect the expression of Cx43, smad4 and PCNA protein in normal and carcinomatous gastric tissue, expression levels mRNA of Cx43, smad4 and PCNA were detected by RT-PCR in normal and carcinomatous gastric tissue. Experimental data were analyzed by combining clinical pathology data using statistical approach. Results: The expression levels of Cx43, and smad4 in carcinomatous gastric tissue were lower than they were in normal gastric tissue. The expression level of PCNA in carcinomatous gastric tissue was higher than that in normal gastric tissue. The expression levels of Cx43, Smad4 and PCNA in groups of age and gender is not significant. The expression of Cx43, Smad4 and PCNA in different clinicopathologic features of carcinomatous gastric tissue including degrees of pathological differentiation, lymph node metastasis condition, depth of tumor invasion and TNM stages is statistically significant. With the progression of gastric carcinoma, the expression levels of Cx43 and Smad4 were decreased, conversely PCNA showed a high expression level. Based on the analysis Cx43 negatively correlated with PCNA, Cx43 positively correlated with Smad4, Smad4 negatively correlated with PCNA. Conclusions: The protein and mRNA expressions of Cx43, smad4 and PCNA were significant differences between normal gastric tissue and gastric carcinoma, also were concerned with differentiation degree, lymph node metastasis, TNM stages and depth of invasion, while not significant with age and gender. This suggests that they may play an important role in occurrence and development of gastric carcinoma, but also may have some interaction. Asian Journal of Medical Sciences Vol.7(1) 2015 6-13